ARCTIC GEOPOLITICS FROM CLASSICAL TO CRITICAL APPROACH – IMPORTANCE OF IMMATERIAL FACTORS - Lassi Heininen (GEOGRAPHY, ENVIRONMENT, SUSTAINABILITY, 2018)
Despite different perceptions, discourses and approaches, the post-Cold War Arctic is with a high geopolitical stability based on institutional, international cooperation started by the Arctic states and supported by Arctic indigenous peoples, non- governmental organizations and sub-national governments. As a result, there are neither armed conflicts nor serious disputes on national borders. Behind the high geopolitical stability are on the one hand, common interests of the Arctic states to decrease military tension and increase political stability by causing a transformation from confrontation to environmental cooperation. On the other hand, there are certain features of Arctic geopolitics as prerequisites for a transformation, such as firm state sovereignty, high degree of legal certainty, and flexibility in agenda setting. When assessing a state of Arctic geopolitics and IR of the post-Cold War era, there is an ambivalence on how ‘geopolitics’ is defined. Behind are the dualism of military presence based on the nuclear weapons’ systems and the high stability based on international, institutional cooperation between the eight Arctic states. As well as, that there are two major competing discourses: first, the Arctic as a ’zone of peace’ and exceptional in world politics, and second, that there is a race of resources and the consequent emerging conflicts in theArctic. In addition, there are fresh reminders that Arctic geopolitics is impacted by (grand) environmental challenges and ‘wicked problems’, in particular climate change; and that new multi- dimensional dynamics has made Arctic geopolitics global. The article aims to draw up a holistic picture of the post-Cold War Arctic, and discuss what might be special features of Arctic geopolitics in globalization. The article examines and discusses the transformation of approach from classical geopolitics to critical geopolitics by applying main approaches of geopolitics to the Arctic/Arctic geopolitics.